Pengaruh Harga dan Promosi terhadap Meningkatnya Kepuasan Pelanggan - Rahma Wulan Suci Nasution; Nuri Aslami (Transformasi Manageria: Journal of Islamic Education Management, 2022)
Along with the development of economy and technology and business competition in the global market, companies are competing in order to provide more satisfactory products and services to the customers and to offer competitive price. This competition is carried out in order to gain new customer and to retain their customer. This research is aimed to find out the influence of sevice quality, product quality and price to the customer satisfaction. The analysis technique has been done by using multiple linear regression analysis.The result of the research shows that the variables which have been applied in this research models are service quality, product quality and price that each of them has significant and positive influence to the customer satisfaction who have ever used the transportation services of Blue Bird taxi in Surabaya.These results indicate that the better quality of service, product, and price then customer satisfaction increases. Keywords: service quality, product quality, price and customer satisfaction.